Regulating Systematic Occupational Health and Safety Management: Comparing the Norwegian and Australian Experience - Saksvik, Per Øystein; Quinlan, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
SummaryThe promotion of systematic occupational health and safety management (SOHSM) represents a comparatively recent but significant realignment of regulatory strategy that has been embraced by many, if not most, industrialized countries. As yet there has been little critical evaluation of the origins and implications of this shift, and to what extent the experience of these measures differs between countries. This article seeks to start the process of answering these questions by comparing SOHSM in Norway and Australia. We identified a number of common challenges (problems of “paper” compliance, limited union input and the growth of precarious employment). In particular, the article highlights the interdependence of OHS and industrial relations regulatory regimes and argues the move away from inclusive collectivist regimes places significant constraints on independent vetting of SOHSM—a crucial element in their effectiveness.